Microstructural Basis of Contusion Expansion in Traumatic Brain Injury: Insights from Diffusion Tensor Imaging. Issue 6 (June 2013) - Newcombe, Virginia FJ; Williams, Guy B; Outtrim, Joanne G; Chatfield, Doris; Abate, M Gulia; Geeraerts, Thomas; Manktelow, Anne; Room, Hywel; Mariappen, Leela; Hutchinson, Peter J; Coles, Jonathan P; Menon, David K
Traumatic brain injury (TBI) is often exacerbated by events that lead to secondary brain injury, and represent potentially modifiable causes of mortality and morbidity. Diffusion tensor imaging was used to characterize tissue at-risk in a group of 35 patients scanned at a median of 50 hours after injury. Injury progression was assessed in a subset of 16 patients with two scans. All contusions within the first few days of injury showed a core of restricted diffusion, surrounded by an area of raised apparent diffusion coefficient (ADC). In addition to these two well-defined regions, a thinner rim of reduced ADC was observed surrounding the region of increased ADC in 91% of patients scanned within the first 3 days after injury. In patients who underwent serial imaging, the rim of ADC hypointensity was subsumed into the high ADC region as the contusion enlarged. Overall contusion enlargement tended to be more frequent with early lesions, but its extent was unrelated to the time of initial imaging, initial contusion size, or the presence of hemostatic abnormalities. This rim of hypointensity may characterize a region of microvascular failure resulting in cytotoxic edema, and may represent a 'traumatic penumbra' which may be rescued by effective therapy.